Solid Oxide Fuel Cells fuelled with biogas: Potential and constraints. (April 2019) - Saadabadi, S. Ali; Thallam Thattai, Aditya; Fan, Liyuan; Lindeboom, Ralph E.F.; Spanjers, Henri; Aravind, P.V.
Abstract: Anaerobic Digestion (AD) is used worldwide for treating organic waste and wastewater. Biogas produced can be converted using conventional energy conversion devices to provide energy efficient, integrated waste solutions. Typically, the electrical conversion-efficiency of these devices is 30–40% and is lowered due to biogas utilization instead of high pure refined natural gas. The Solid Oxide Fuel Cell (SOFC) as an alternative device offers high (50–60%) electrical efficiency with low emissions (CO2, NOx) and high temperature residual heat. The high quality residual heat from SOFCs could be used to improve biogas production through thermal pre-treatment of the substrate for anaerobic digestion. This work discusses the advantages and challenges of integrated AD-SOFC systems against the most recent scientific and practical developments in the AD and SOFC domain. First, the biogas production process and its influence on the composition and level of contaminants in biogas are explained. Subsequently, the potential of various biogas cleaning techniques is discussed in order to remove contaminants that threaten stable and long-term SOFC operation. Since SOFCs utilize H2 and/or CO as fuel, possibilities for internal and external reforming are explained in detail. Special attention is given to biogas dry reforming in which CO2 naturally present in the biogas is utilized effectively in the reforming process. A detailed discussion on the choice of SOFC materials is presented, with a focus on biogas internal reforming. Various integrated SOFC system models with multiple configurations are also reviewed indicating the overall efficiencies. Some biogas SOFC pilot-plants are described and discussed to conclude with the techno-economic aspects of biogas SOFC systems. Highlights: An overview of the development and challenges of integrated AD-SOFC system. The use of high-quality heat from SOFC in thermal pre-treatment of sludge in AD. Biogas fuel processing, including the biogas cleaning and methane reforming methods. A detailed discussion on internal dry methane reforming focusing on carbon deposition. The use of mixed ammonia-biogas in SOFC to promote the self-sustainability of WWTP.